Homemade Household Cleaners - Amanda Griffin; Randall A. Cantrell (EDIS, 2014)
Are you on a budget? Running low on those household cleaners? Instead of heading to the store to buy those more expensive cleaners, make your own! Many homemade household cleaners can be made with just a few inexpensive products that will last a lot longer. This 3-page fact sheet was written by Amanda Griffin and Randall A. Cantrell, and published by the UF Department of Family, Youth and Community Sciences, October 2014. (Photo: iStock/Thinkstock.com)